Unraveling the role of IL-17 in lichen planus - Tolušić Levak, Maja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Lichen planus (LP) is a chronic T cell–mediated inflammatory disease affecting the skin and mucosa. Interleukin-17 (IL-17), a pro-inflammatory cytokine, has been implicated in LP pathogenesis, but its tissue-level expression across clinical variants remains underexplored. This study compares IL-17 expression in healthy skin and LP lesions and assesses variations based on clinical presentation. Methods: This cross-sectional retrospective study included 20 LP skin samples and 10 healthy controls. The sample collection spanned a period of 10 years. IL-17 expression was assessed via immunohistochemistry and quantified using a modified Q score. Samples were categorized by mucosal involvement and lesion distribution. Statistical analysis was performed with the MannWhitney U test. Results: IL-17 was absent in healthy skin but present in all LP samples. IL-17 expression was significantly higher in patients with both skin and oral mucosal involvement compared to those with cutaneous LP (p = 0.003). No significant difference was observed between generalized and localized LP. Conclusions: The results indicate a distinct increase in IL-17 expression in LP lesions, particularly with mucosal involvement, supporting its role in LP pathogenesis. These findings suggest IL-17 as a potential biomarker and therapeutic target, warranting further investigation in larger cohorts.
Keywords: immunoexpression; imunoekspresija; inflammatory dermatoses; interleukin-17; interlevkin-17; lichen planus; vnetne dermatoze